(untitled) (Journal of Partial Differential Equations, 1990)
ln this peper we obtained the Hopf bifurcation theorem for an abstract functional differential equation by the results of [1]. The asymptotic expression of bifurcation formulae and stability condition were given in detail. Applying the result, we considered the Hopf bifurcation problem for a reaction-diffusion equation with time delay.